2023
DOI: 10.3389/fendo.2023.1110624
|View full text |Cite
|
Sign up to set email alerts
|

A real-world study of anlotinib combined with GS regimen as first-line treatment for advanced pancreatic cancer

Abstract: BackgroundAnlotinib may boost the efficacy of pancreatic cancer (PC) treatment if timely added to the GS regimen (Gemcitabine, Tegafur-gimeracil-oteracil potassium); however, no data has been published. This study evaluated the safety and efficacy of anlotinib in combination with the GS regimen(hereafter referred to as the A+GS regimen) in the first-line treatment of patients with unresectable or metastatic PC.MethodsPatients with unresectable or metastatic PC treated at Yueyang Central Hospital and Yueyang Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…We also found that the addition of anlotinib to second‐line therapy was associated with longer OS compared with later‐line anlotinib ( p = 0.012). Our findings suggest that additional anlotinib may be a valid add‐on option recommended for PDAC patients, which shows similar results as reported by Zhan et al [ 25 ]. The advantage of anlotinib combination therapy may be due to the fact that PDAC has a special tumor microenvironment with dense interstitium, which is an important reason for the poor response of chemotherapy alone [ 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…We also found that the addition of anlotinib to second‐line therapy was associated with longer OS compared with later‐line anlotinib ( p = 0.012). Our findings suggest that additional anlotinib may be a valid add‐on option recommended for PDAC patients, which shows similar results as reported by Zhan et al [ 25 ]. The advantage of anlotinib combination therapy may be due to the fact that PDAC has a special tumor microenvironment with dense interstitium, which is an important reason for the poor response of chemotherapy alone [ 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…[9] However, this binary M1/M2 classification is increasingly viewed as an oversimplification and is insufficient to capture the nuanced roles and heterogeneity of macrophages in sepsis. [10,11] Emerging evidence suggests that macrophages can polarize into a spectrum of functional states, influenced by their microenvironment. [12,13] This cellular heterogeneity may contribute to the complexity and variability in sepsis outcomes.…”
Section: Introductionmentioning
confidence: 99%